Ordinance no. 2: An Ordinance Relating to Concealed Weapons, in THE ENTERPRISE, Oct. 20, 1909 at 1, § 1 - (:unkn) unknown (My University, 1909)
No person in this town shall wear under his clothes or concealed on or about his person, any pistol or revolver, except by special permission from the Mayor; nor shall any person wear under his clothes or concealed on or about his person, any slungshot, cross-knuckles of lead, brass or other metal, or any bowie knife, razor, billy, dirk , dirk-knife or dagger, or any knife resembling a bowie-knife, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED